EFFECT OF VARIATION FORM (QUADRILATERAL AND HEXAGON), PARTICLE SIZE AND PRESSURE ON THE CHARACTERISTICS OF BURNING CHARCOAL WOOD WASTE BRIQUETTES ALABAN AND RICE HUSK - Akhmad Syarief; A’yan Sabitah; Luqmanul Hakim; Fadliyanur Fadliyanur; Dhanu Suryanta Suryanta; Defrihans Galang P; Hansen Rivaldo Napitulu; Aulia Aufa Ramadhasari; Ichwan Noor Ardiyat (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2021)
Briquettes have been researched and developed as a substitute for solid fuels such as wood. One of them is briquettes made from processing waste such as sawdust, rice husks and even industrial waste. In this journal research, researchers are interested in knowing the characteristics of burning briquettes made from rice husk mixed with alaban wood charcoal waste which includes initial ignition, combustion rate and combustion temperature. The briquette samples used were varied in the form of rectangular and hexagonal shapes, mesh 20 and mesh 40 and the briquette printing pressure of 50 kg/cm2 and 100 kg/cm2. The results showed that the highest temperature for rectangular briquettes with a mesh of 40 and a compressive strength of 50 kg/cm2 was 412ºC and the lowest for rectangular briquettes with a mesh of 20 and a compressive strength of 100 kg/cm2. 333.33 ºC. Pressure strength affects the ignition speed, the faster the initial ignition and the longer the combustion rate due to the presence of air voids and the high moulding pressure affects the duration of the combustion process.